2020
DOI: 10.1017/s0967199420000441
|View full text |Cite
|
Sign up to set email alerts
|

Role of diagnostic intracytoplasmic sperm injection (ICSI) in the management of genetically determined zona pellucida-free oocytes during in vitro fertilization: a case report

Abstract: Purpose: To report the utilization of diagnostic intracytoplasmic sperm injection (D-ICSI), an ICSI cycle performed in the natural cycle, to obtain information about embryo development potential after sperm injection into zona pellucida (ZP)-free oocytes. Materials and Methods: We report the case of a couple with primary unexplained infertility with a history of previous failed, in vitro fertilization intracytoplasmic sperm injection (IVF-ICSI) cycles characterized by the presence of ZP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Mutations in the ZP1 gene can lead to two abnormal oocyte phenotypes: zona pellucida deficiency and empty follicle syndrome (EFS). The novel mutation we present in this study has been identified in the trefoil domain of ZP1, similar to what were previously reported ( Metwalley et al, 2020 ; Xu et al, 2020 ). Interestingly, the trefoil domain is unique to the hZP1 protein and is not found in hZP2 and hZP3.…”
Section: Discussionsupporting
confidence: 90%
“…Mutations in the ZP1 gene can lead to two abnormal oocyte phenotypes: zona pellucida deficiency and empty follicle syndrome (EFS). The novel mutation we present in this study has been identified in the trefoil domain of ZP1, similar to what were previously reported ( Metwalley et al, 2020 ; Xu et al, 2020 ). Interestingly, the trefoil domain is unique to the hZP1 protein and is not found in hZP2 and hZP3.…”
Section: Discussionsupporting
confidence: 90%
“…The third patient carried homozygous missense mutation c.706 T > C; after the first failed ART, diagnostic intracytoplasmic sperm injection (D-ICSI) was used in the normal menstrual cycle to explore the feasibility of embryo development, then a new ART cycle was started to obtain 8 ZFO, 6 of them were fertilized successfully via ICSI, and finally delivered a healthy baby at 38 weeks of gestation by cesarean section. Additionally, we get the information from the author’s email that she is currently pregnant with twins through ICSI with the modified protocol [ 30 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…If oocytes with ZP defects could be obtained from the affected patients, ICSI could be preferentially chosen instead of the traditional IVF, which may improve the probability of successful pregnancy via ART. Metwalley et al proposed a new method called D-ICSI, an ICSI cycle performed in the natural cycle, to obtain information about embryo development potential before therapeutic ICSI [ 34 ]. For patients with the most severe phenotypes of EFS caused by ZP gene mutations, the current optimal treatment choice would be egg donation.…”
Section: Discussionmentioning
confidence: 99%